Influence of artificial aging on the in vitro fracture load of tooth-to-implant-supported fixed partial dentures with different retainer designs - Waldecker, Moritz; Custodio, Lorie Jane; Ohlmann, Brigitte; Rammelsberg, Peter; Rues, Stefan (The journal of prosthetic dentistry, 2025)
Statement of problem - Tooth-to-implant-supported fixed partial dentures (TI-FPDs) are a valuable treatment option for the shortened dental arch. For naturally healthy abutment teeth or abutment teeth with small restorations, inlays or adhesive wings present - as opposed to complete crowns - minimally invasive FPD retainer elements. Data on TI-FPDs with minimally invasive retainer designs are sparse. - Purpose - The purpose of this in vitro study was to compare test forces correlating with fracture (ultimate load, Fu) or formation of initial damage (force at first damage, F1d) and the failure modes of TI-FPDs with different retainer designs fabricated using either monolithic zirconia (mZir) or veneered cobalt chromium alloy frameworks (vCo-Cr). - Material and methods - The situation of a 3-unit FPD to replace a maxillary first molar with the second premolar as an abutment tooth and an implant in the region of the second molar was simulated. For mZir-TI-FPDs, 3 different retainer designs of the second premolar, inlay (IR), adhesive wing (WR) and complete crown (CC), were examined (n=8). In addition, the restorations with an adhesive wing and complete crown were also fabricated in metal-ceramic (n=8). After FPD fabrication and adhesive cementation to Co-Cr die replicas covered by shrink wrap tubes to simulate tooth mobility and implants with standard abutments, all 5 test groups were subjected to fracture load tests without artificial aging. The fracture load (Fu) was determined under oblique loading of the mesiopalatal cusp of the pontic. Additional FPDs (n=8) were fabricated for the inlay and adhesive wing retainer designs and subjected to artificial aging consisting of 150 days water storage at 37 °C including thermocycling (37 500×6.5 °C and 60 °C) and mastication simulation (1 200 000×108 N) after adhesive cementation. Specimens surviving artificial aging were subjected to fracture load tests as described previously. - Results - For monolithic zirconia restorations, the first damage to the restoration was always fracture. Mean fracture resistances for mZir-WR-TI-FPDs were Fu,mean=996 N without aging and Fu,mean=1033 N after aging. Slightly higher load-bearing capacity was observed for mZir-IR-TI-FPDs with Fu,mean=1067 N without aging and Fu,mean=1192 N after aging. Without exception, vCo-Cr-WR-TI-FPDs were either predamaged (cracks within the veneering ceramics, F1d=108 N) or showed major chipping which was defined as fracture (Fu=F1d=108 N) after mastication simulation, achieving Fu,mean=806 N after aging in contrast with Fu,mean=1222 N for the unaged counterparts. Unaged mZir-CC-TI-FPDs were associated with Fu,mean=1159 N compared with Fu=1860 N for vCo-Cr-CC-TI-FPDs. However, for this metal-ceramic group, cracking of the veneer started at F1d,mean=1126 N. - Conclusions - All TI-FPDs showed clinically acceptable load-bearing capacity. Complications can occur with veneered TI-FPDs in the form of chipping even with low masticatory forces.
Online verfügbar: 13. Mai 2025, Artikelversion: 5. August 2025
Gesehen am 08.01.2026